Association among Orthodontic Malocclusions, Paranasal Sinuses Anatomic Variations and Adenoid Vegetation in Children Using CBCT - Serdal Kenan Kose; Secil Aksoy; Merve Onder; Ulas Oz; Kaan Orhan (Children, 2023)
The aim of this study is to evaluate the relationship between orthodontic malocclusion, paranasal sinus (PS) variations, and adenoid vegetation in a group of pediatric patients with chronic rhinosinusitis. Clinical and radiographical data were retrospectively evaluated and 58 patients were diagnosed as having chronic sinus disease. Cone-beam computed tomography (CBCT) images were acquired with Newtom-3G. Anatomical variations of the PS were assessed on every section. Additionally, for cephalometric analysis, the images were imported into the InVivoDental software program. A total of 252 anatomical variations, which encompassed 19 different types, were detected in the current study. Concha bullosa was the most common anatomical variation, at 72.4%. Septum deviation was the second most common one, at 67.2%. The Class III group exhibited a significantly higher prevalence of concha bullosa and secondary middle turbinate than the other groups. While adenoid vegetation was most common in the Class III group, sinusitis and antral disease were most common in the Class II group. Overall, Class III subjects exhibited fewer PS variations. In conclusion, concha bullosa emerged as the most prevalent anatomical variation, with distinctive patterns observed across different malocclusion groups. Therefore, CBCT is useful, especially in pediatric patients, due to its low dose advantage.